2017
DOI: 10.1002/dneu.22490
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish transgenic constructs label specific neurons in Xenopus laevis spinal cord and identify frog V0v spinal neurons

Abstract: A correctly functioning spinal cord is crucial for locomotion and communication between body and brain but there are fundamental gaps in our knowledge of how spinal neuronal circuitry is established and functions. To understand the genetic program that regulates specification and functions of this circuitry, we need to connect neuronal molecular phenotypes with physiological analyses. Studies using Xenopus laevis tadpoles have increased our understanding of spinal cord neuronal physiology and function, particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 98 publications
1
7
0
Order By: Relevance
“…These neurons are integrated into zebrafish motor networks early during development and are recruited during spontaneous, whole-body bends [16], which resemble escape bends used in response to threats in older fish. Recent work from the Lewis lab has revealed that V0v neurons in frog embryos are also primarily ascending [17,18], which is a time of life when frogs engage axially-based escape movements [19,20]. These results are consistent with the idea of a conserved function for early-born Eve/Evx interneurons during powerful escape behaviors.…”
Section: Even-skipped Interneurons and Swimmingsupporting
confidence: 65%
“…These neurons are integrated into zebrafish motor networks early during development and are recruited during spontaneous, whole-body bends [16], which resemble escape bends used in response to threats in older fish. Recent work from the Lewis lab has revealed that V0v neurons in frog embryos are also primarily ascending [17,18], which is a time of life when frogs engage axially-based escape movements [19,20]. These results are consistent with the idea of a conserved function for early-born Eve/Evx interneurons during powerful escape behaviors.…”
Section: Even-skipped Interneurons and Swimmingsupporting
confidence: 65%
“…Plasmid DNA and transposase mRNA for microinjection was prepared as in (Juárez‐Morales et al, 2017; Kwan et al, 2007). Approximately 10 nl of a combination of plasmid DNA (60–80 ng/μl) and transposase mRNA (30 ng/μl) was injected into both blastomeres of 1–2‐cell stage zebrafish embryos.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with these conserved expression patterns, the types of neurons found in the spinal cord, and the functions of particular transcription factors in specifying these neuronal subtypes has also been highly conserved throughout vertebrate evolution (e.g. England et al, 2014;Gosgnach et al, 2006;Goulding and Pfaff, 2005;Juarez-Morales et al, 2017;Lewis, 2006;Li et al, 2004)}. However, most of these comparative analyses have so far been limited to ventral spinal cord and it is still unclear whether dorsal spinal cord neurons are as highly conserved.…”
Section: Introductionmentioning
confidence: 92%
“…Plasmid DNA and transposase mRNA for microinjection was prepared as in (Juarez-Morales et al, 2017;Kwan et al, 2007…”
Section: Creation Of Tg(16 Lbx1a:egfp) Su33 Transgenic Linementioning
confidence: 99%
See 1 more Smart Citation